Regeneration of Pancreatic β-Islet Cells in a Type-II Diabetic - Edwin C. Jones; J. Craig Rylands; Cortney L. Jardet (Case Reports in Endocrinology)
A case report is presented in which a type-II diabetic patient significantly improved his dysfunctional β-islet cells using a combination of a strenuous exercise program, cyclical ketogenic diet, and oral GABA/probiotic supplementation. The patient was diagnosed with type-II diabetes at the age of 41 which then progressed through a typical series of treatment changes over 14 years. Treatment periods consisted of metformin therapy alone for 4 years followed by a metformin/glyburide combination therapy for 6 years, and eventually an insulin/metformin combination therapy for 4 years. One year after the initiation of insulin, the patient increased the level of strenuous physical activity (hiking and weight lifting) and adopted a ketogenic diet. Oral GABA and probiotic supplementation were also initiated at the age of 52.7. By the age of 55, the patient no longer required any insulin and is currently being managed with metformin alone. C-peptide values indicate a functional improvement of the β-islet cells during the time of insulin/GABA/probiotic treatment.